Nd : Yag Laser Posterior Capsulotomy A Clinical Study (International Journal of Scientific Research and Management (IJSRM), 2015)
Nd:YAG laser capsulotomy was carried out in 100 eyes of 99 patients in the Department of Ophthalmology,government General Hospital,Kakinada.Among them 2 cases are aphakic and the rest were pseudophakic.Out of the pseudophakics one of the patients has undergone triple procedure .The cases were followed up between October 2010 to September 2012.Average period follow up was 6 months.